Strengthening holistic assessment in Islamic religious education: Cognitive, psychomotor, and affective domains - Marprilyan Muharrozi; Saepul Anwar; Usup Romli (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2025)
Assessment in Islamic Religious Education (Pendidikan Agama Islam/PAI) plays a crucial role in fostering not only students’ cognitive achievement but also their practical religious skills and moral character. However, implementing holistic assessment across cognitive, psychomotor, and affective domains remains challenging within real school contexts. This study aims to examine barriers, strategies, and contextual factors influencing the implementation of PAI assessment at the junior secondary level. Employing a qualitative instrumental case study design, the study involved four PAI teachers at a public junior secondary school in Bandung, Indonesia. Data were collected through semi-structured interviews and document analysis, and analyzed inductively using Miles and Huberman’s interactive model with source and method triangulation to ensure trustworthiness. The findings reveal that cognitive assessment is constrained by students’ heterogeneous abilities and limited instructional time; psychomotor assessment is challenged by uneven student readiness and insufficient foundational religious skills; while affective assessment is hindered by subjectivity, diverse student attitudes, and the absence of standardized assessment guidelines. These domain-specific challenges are further compounded by contextual factors such as weak Qur’anic literacy, limited parental support, student absenteeism, and conflicts with school agendas. Despite these obstacles, teachers adopted adaptive strategies including differentiated assessment, remedial support, peer tutoring, parental collaboration, and integration of assessment into daily religious practices. The study concludes that effective PAI assessment requires a holistic, adaptive, and collaborative approach that integrates all learning domains while remaining sensitive to socio-religious and institutional contexts. The findings highlight implications for teacher professional development, refinement of assessment rubrics, and supportive school policies to strengthen sustainable and authentic PAI assessment practices.